Association between chronic periodontitis and serum lipid levels - Pejčić Ana; Kesić Ljiljana; Ilić Stevan; Pešić Zoran; Mirković Dimitrije (Vojnosanitetski Pregled)
Background/Aim. Periodontitis is a local inflammatory process mediating destruction of periodontal tissues triggered by bacterial insult. However, this disease is also characterized by systemic inflammatory host responses that may contrbute, in part, to the recently reported increased risk for systemic diseases, including an altered lipid metabolism. On the other hand, many people in the world are affected by hyperlipidemia, which is a known risk faktor for atherosclerosis. The aim of this study was to determine the relationship between periodontal disease and blood lipid levels. Methods. A total of 50 patients with periodontitis included in this study had no documented history of recent acute coronary events. The healthy, non-periodontal subjects (comparison group) comprised 25 subjects. All the patients were periodontology examined and completed a medical history. Dental plaque index, probing depth, gingival index bleeding on probing and clinical attechment levels were recorded. Blood samples were taken on admission for measurements of serum total cholesterol, triglycerides, hight density lipoprotein cholesterol (HDL-cholesterol), and low density lipoprotein cholesterol (LDL-cholesterol). Results. The obtained results showed that mean levels of cholesterol (6.09 ± 1.61 mmol/L), triglycerdes (2.19+1.67mmol/l) and LDL cholesterol (4.09 ± 1.40 mmol/L) in individuals with periodontitis were higer, and levels od HDL (1.43 ± 0.51 mmol/L) was lower than those of individuals without periodontitis (4.86 ± 1.37; 1.14 ± 0.71; 3.18 ± 0.64; 1.53 ± 0.32 mmol/L, respectively). Conclusion. This study confirms a significant relationship between periodontal disease, regardless its intensity, and blood lipid levels in the studied population. The results imply that periodontitis may be a risk factor and may contribute to the pathogenesis of atherosclerosis and cardiovascular diseases (CVD). However, future prospective randomized studies have to determine whether periodontal disease is a risk factor for the occurrence of CVD.